Who is benefiting more from common property forest resources: poor or less poor? - Bhandari, AR; Uibrig, H (Banko Janakari, 2009)
This paper intends to assess the distribution of community forestry benefits among economic groups of the users comparing protected area buffer zone with the Department of Forests regime in Nepal. Following the case study approach two forest user groups of Nawalparasi district, each from buffer zone of Chitwan National Park and Department of Forests regime were selected for the study. The study results suggest that the users in the buffer zone receive less benefit from community forestry than the users in the Department of Forests regime. Analysis of inputs and outputs reveals that poor households receive less benefit than the better off households in both of the regimes. Insofar the results counteract the principles of equity as expected from national forest policy goals and approaches. Key words: benefits, buffer zone, community forestry, equity, heterogeneity, Nepal. doi: 10.3126/banko.v18i1.2165 Banko Janakari, Vol. 18, No. 1, 42-47